2013
DOI: 10.1007/s00442-013-2728-2
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated by nature and agriculture: performance of a specialist herbivore improves with host-plant life history evolution, domestication, and breeding

Abstract: Plant defenses against herbivores are predicted to change as plant lineages diversify, and with domestication and subsequent selection and breeding in the case of crop plants. We addressed whether defense against a specialist herbivore declined coincidently with life history evolution, domestication, and breeding within the grass genus Zea (Poaceae). For this, we assessed performance of corn leafhopper (Dalbulus maidis) following colonization of one of four Zea species containing three successive transitions: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 55 publications
5
68
0
Order By: Relevance
“…Our study indicated that the specialist herbivore D. maidis has a clear preference for maize over the teosintes, which suggests a lower level of anti-herbivore defense in the former, as suggested previously, also for other insects (Rosenthal & Dirzo, 1997;Szczepaniec et al, 2012;Takahashi et al, 2012;D avila-Flores et al, 2013). Additionally, our study did not address differences in chemical defenses nor nutritional value among host plants, which may further explain the oviposition preference that we found.…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…Our study indicated that the specialist herbivore D. maidis has a clear preference for maize over the teosintes, which suggests a lower level of anti-herbivore defense in the former, as suggested previously, also for other insects (Rosenthal & Dirzo, 1997;Szczepaniec et al, 2012;Takahashi et al, 2012;D avila-Flores et al, 2013). Additionally, our study did not address differences in chemical defenses nor nutritional value among host plants, which may further explain the oviposition preference that we found.…”
Section: Discussionsupporting
confidence: 41%
“…At the highest trichome density found in this study, one trichome per 1.9 mm (ca. Although our study does not shed light on the relevance of these hypotheses to our results, a recent study involving D. maidis and the suite of Zea plants studied herein suggests that host preference may be mediated by offspring performance because the performance of D. maidis was better on maizes compared to teosintes (D avila-Flores et al, 2013). 3 mm long 9 1 mm wide may still have sufficient space to maneuver unimpeded over the leaf surface, between trichomes, to feed and lay eggs.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Insect herbivores typically perform better on agricultural plants than on wild ancestors, due to reductions in secondary compounds during crop domestication (Harvey et al, 2007;Rodriguez-Saona et al, 2011;Dávila-Flores et al, 2013;Szczepaniec et al, 2013;Turcotte et al, 2014). Crop domestication may facilitate herbivore populations in other ways as well.…”
Section: Crop Domesticationmentioning
confidence: 99%
“…Selective breeding reduces genetic diversity of domesticated crops, which results in lacking or weakly defensive traits (DOEBLEY et al, 2004 DIRZO, 1997;TAMIRU et al, 2011;SZCZEPANIEC et al, 2013;DÁVILA-FLORES et al, 2013;MUTYAMBAI et al, 2015). Hence, plant domestication also affects species interactions in tritrophic systems (BENREY et al, 1998;CHEN et al, 2015).…”
Section: Interações Tróficas Em Plantas Zea Spp Envolvendo Os Herbivmentioning
confidence: 99%